Is it time to let go? The Best Loser System in Mauritius - Fessha, Yonatan; Nam, Nora Ho Tu (Afrika Focus, 2015)
As Mauritius was moving towards independence, one contested issue was the electoral system to be adopted. Minority groups were wary of any electoral system which would allow for a Hindu- hegemony and which would leave them unable to access power. To respond to this anxiety, Mauritius adopted the best loser system (BLS), a unique system of ethnic representation in the national parliament. This contribution examines how the adoption of BLS, has over the years, contributed to the management of ethnic diversity. More importantly, it examines the current debate regarding the contemporary relevance of BLS to today’s Mauritius. At times heavily criticized for its commu- nal and ethnic undertones, BLS has ensured continued minority representation in parliament. The article argues that one must be cautious about dismissing the relevance of inclusive institutions such as BLS as such an attitude might well undermine the move towards a more united Mauritius.